GIS-based aquaculture site suitability study using multi-criteria evaluation approach - Nayak, Ashok K.; Pant, D.; Kumar, P.; Mahanta, P. C.; Pandey, N. N. (Indian Journal of Fisheries, 2013)
The present study identifies and quantifies appropriate sites for aquaculture development in the Upland Himalayan region of Uttarakhand using remote sensing, GPS and geographical information systems (GIS). The GIS has an increasingly important role in management and utilization of natural resources significantly in fisheries resource assessment and management. Aquaculture has become one of the fastest growing food industries in the world. For aquaculture development in the region, the importance of each parameter of soil quality, water quality and infrastructure facilities were accessed using analytical hierarchical process. Various thematic layers were prepared for categorizing suitable aquaculture sites based on three sub-models viz. soil quality, water quality and infrastructure facilities. The site suitability map for aquaculture development was prepared for Betalghat block of Nainital district, Uttarakhand. The total area suitable for aquaculture development were computed as most suitable of 8426 ha (27%); moderately suitable of 5623 ha (18%) and not suitable of 198 ha (1%) with a constraints of forest cover and infrastructure facilities of around 16617 ha (54%) of the total land area.